Field‐realistic neonicotinoid exposure has sub‐lethal effects on non‐Apis bees: A meta‐analysis. (6th September 2021) - Siviter, Harry; Richman, Sarah K.; Muth, Felicity
Abstract: Neonicotinoid insecticides can have sub‐lethal effects on bees which has led to calls from conservationists for a global ban. In contrast, agrochemical companies argue that neonicotinoids do not harm honeybees at field‐realistic levels. However, the focus on honeybees neglects the potential impact on other bee species. We conducted a meta‐analysis to assess whether field‐realistic neonicotinoid exposure has sub‐lethal effects on non‐ Apis bees. We extracted data from 53 papers (212 effects sizes) and found that it largely consisted of two genera: bumblebees ( Bombus) and mason bees ( Osmia), highlighting a substantial taxonomic knowledge gap. Neonicotinoid exposure negatively affected reproductive output across all bees and impaired bumblebee colony growth and foraging. Neonicotinoids also reduced Bombus, but not Osmia, individual development (growth and body size). Our results suggest that restrictions on neonicotinoids should benefit bee populations and highlight that the current regulatory process does not safeguard pollinators from the unwanted consequences of insecticide use. Abstract : We conducted a meta‐analysis to assess whether field‐realistic neonicotinoid exposure has sub‐lethal effects on non‐Apis bees. Neonicotinoid exposure negatively affected reproductive output across all bees and impaired bumblebee colony growth and foraging. Our results suggest that restrictions on neonicotinoids will benefit bee populations and highlight that the current regulatory process does not safeguard pollinators from the unwanted consequences of insecticide use.